Degradation of water resources in rural Burkina Faso: drivers, local perceptions and solutions. - Balana, Bedru; Debevec, Liza; Somda-Kabore , Letisia Rolande (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Burkina Faso reformed its water management institutions and adopted integrated water resources management (IWRM) for more than two decades, yet the country still suffers from weak institutions and ineffective implementation of water management reforms. The key institutional question is: “How can IWRM reforms be adapted to increase effectiveness and sustainability of water management, and improve livelihoods of rural populations through increased participation of local stakeholders?” A key practical issue related to this bigger institutional question is to understand the barriers to adoption of good land and water management measures by riparian farmers and other land/water users, and the mechanisms to induce behavioral change among these users. Knowledge gaps exist in understanding the local perceptions and preferences of alternative management measures, and the incentive mechanisms to induce behavioral change. The aim of this study, which was part of a 3-year project entitled ‘Participatory planning for more inclusive and sustainable water management in rural Burkina Faso’, was to understand the perceptions, preferences and willingness of farmers and other land/water users to adopt environmentally friendly land and water management measures. The study also examined potential mechanisms that could induce riparian economic actors to adopt such measures.